Trends in the development of equipment for feeding cattle - Boltianskyi, Oleh; Болтянський, Олег Володимирович; Болтянский, Олег Владимирович; Boltianska, Natalia; Болтянська, Наталя Іванівна; Болтянская, Наталья Ивановна (ТДАТУ, 2021)
Recently, automated animal feeding systems have been developed, which are moved not by suspended guides, but in an autonomous mode using modern control systems for the movement of mobile objects. Moreover, when creating the design of such robots, the basis was not suspended feed-feeders, but mobile mixers-feeders. Such innovative developments have already been demonstrated at major international exhibitions.
Keywords: livestock based; technology of preparation of feed; dairy industry; milk production have